2016
DOI: 10.1016/j.bbapap.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble and single-molecule biophysical characterization of D17.4 DNA aptamer–IgE interactions

Abstract: The activation parameters obtained by applying transition state analysis to kinetic data can provide details on mechanisms of molecular recognition and have applications in drug design. Single-molecule dissociation kinetics showed greater kinetic complexity than was observed in the ensemble in-solution systems, potentially reflecting conformational heterogeneity of the aptamer. This article is part of a Special Issue entitled: Physiological Enzymology and Protein Functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Our value of k 0 is much higher than the k 0 = 5.4 × 10 −6 s −1 for streptavidin/biotin complex [56], meaning that the DNA-Ab complexes are much weaker. However, the off-rate obtained is within the range reported for DNA-antibody or DNA-protein interactions, for example, the k off of D17.4 DNA aptamer/IgE complex was calculated to be (2.92 ± 0.18) × 10 −3 s −1 or (2.85 ± 0.14) × 10 −3 s −1 depending on the environmental conditions [57, 58]. Giuntoli et al [59] showed that the rate of dissociation from DNA of the Escherichia coli nucleoid protein Fis was approximately k off ~ 8 × 10 −3 s −1 .…”
Section: Discussionmentioning
confidence: 62%
“…Our value of k 0 is much higher than the k 0 = 5.4 × 10 −6 s −1 for streptavidin/biotin complex [56], meaning that the DNA-Ab complexes are much weaker. However, the off-rate obtained is within the range reported for DNA-antibody or DNA-protein interactions, for example, the k off of D17.4 DNA aptamer/IgE complex was calculated to be (2.92 ± 0.18) × 10 −3 s −1 or (2.85 ± 0.14) × 10 −3 s −1 depending on the environmental conditions [57, 58]. Giuntoli et al [59] showed that the rate of dissociation from DNA of the Escherichia coli nucleoid protein Fis was approximately k off ~ 8 × 10 −3 s −1 .…”
Section: Discussionmentioning
confidence: 62%
“…Other drug candidates targeting IgE include DNA aptamer [ 118 ]. However, the structural basis for antagonizing IgE binding to FcεRI has not been well characterized [ 119 , 120 , 121 ].…”
Section: Ige-binding Therapeuticsmentioning
confidence: 99%
“…When the NaCl concentration was increased from 50 to 300 mM, a five-fold increase in the k D value was detected, which might be due to differences in the loop conformation, essential for the IgE binding. Moreover, it was shown that the Fc domain is positively charged, thereby the binding of the aptamer to IgE is partly based on electrostatic interaction which is significantly influenced by the ionic strength [135]. Increasing the temperature resulted in an apparent increase of the k D , since the conformational flexibility and the dye motion is in strong correlation with the temperature [133,135].…”
Section: Detection Principlementioning
confidence: 99%